Microplastic Distribution in Khlong Wong, Songkhla Lake, Thailand: Implications for Household and Fishing-Related Sources - Rodcharoen, Eknarin; Duanghwang, Panisa; Roekngandee, Phatcharee; Wichachucherd, Bongkot (Journal of Fisheries and Environment, 2026)
Microplastic pollution has emerged as a global environmental concern affecting aquatic ecosystems. Khlong Wong, a major canal draining into Songkhla Lake in southern Thailand, may serve as an important transport pathway for land-based microplastics into the lake system. This study aimed to investigate the spatial and temporal distribution of microplastics in the water column of Khlong Wong and examine their relationships with environmental factors. Water samples were collected bimonthly for one year from seven sampling stations along the canal, together with measurements of key water quality parameters. Five types of microplastics were identified: polyester, cotton, nylon, alkyd, and polypropylene (PP). Polyester fibers were the dominant type, accounting for 53.94% of total microplastics, suggesting inputs from household activities and fishing practices. Spatial analysis showed high similarity in microplastic composition along the canal (79.52%–94.88%), with the greatest observed accumulation at the canal mouth, indicating its possible role as a convergence zone before discharge into Songkhla Lake. Temporal analysis showed descriptive seasonal variation, with the greatest observed microplastic abundance recorded during the northeast monsoon in December (36.14±7.69 items∙100 L⁻¹), dominated by polyester fibers likely transported by increased runoff. In contrast, PP and nylon were more prevalent during the hot season (February–April), possibly associated with degradation of fishing gear under prolonged sunlight exposure. Overall, the results suggest that Khlong Wong may function as an important transport pathway conveying microplastics from terrestrial sources and fishing practices into Songkhla Lake. This study provides baseline information to support water quality management and strategies to mitigate microplastic contamination.